Determining the Location of a 220 KV Overhead Line Fault Using the Wave (Traveling Wave) Method - Salmanov, Farid (My University, 2026)
This thesis presents a procedure for the accurate computation of 220 kV overhead transmission line fault location using the traveling wave (TW) method of fault location. Compared to traditional impedance-based methods with high sensitivity to fault resistance, load flow, and system parameters, the traveling wave method is highly accurate based on the physical electromagnetic transients propagation time. The traveling wave technique depends on the observation of the high-frequency voltage and current transients created during fault, traveling along the line nearly at light speed. The accurate location of a fault can be computed by measuring the time-of-arrival of the first wavefronts at the line terminals. Essential to such precise high accuracy is sub-microsecond resolution offered by cutting-edge GPS time synchronization and MHz-range high-frequency data sampling that avoid the limitations of earlier TW systems. The research makes use of the two-ended fault location technique, which sets the first wave front arrival times at both local (tL) and remote (tR) line ends. The core of the research is the Simulink model developed in MATLAB to simulate 220 kV transmission line using the distributed parameter model. This model has a specific Traveling Wave Fault Locator (TWFL) subsystem for calculating propagation velocity from line inductance and capacitance and end fault distance. This simulation confirms the high accuracy of the principle, where it is able to identify faults with a precision of several hundred meters and contribute towards quicker restoration of systems and lower outage duration. The work acknowledges significant challenges, including expense and complexity of the high-speed data acquisition equipment required, and possibility of signal noise and wave reflection leading to inaccuracy. Future research directions, like combining machine learning with hybrid TW-impedance schemes, are mentioned as one possible means of further enhancing this significant power system protection technology's reliability and application.
Keywords: Signal processing -- High frequency techniques.; High voltage engineering -- Measurement.; Power system protection.; Traveling waves (Electric lines) -- Measurement.; Electric power transmission lines -- Fault location.